2016
DOI: 10.1163/15685411-00002946
|View full text |Cite
|
Sign up to set email alerts
|

Neoalloionema tricaudatum gen. n., sp. n. (Nematoda: Alloionematidae) associated with a cyclophorid snail in Cuc Phuong Natural Park, Vietnam

Abstract: A new nematode genus and species associated with terrestrial gastropods from Vietnam is described and illustrated. Partial SSU and ITS rDNA sequences were obtained and subjected to phylogenetic analysis. Both morphologically and molecularly, Neoalloionema tricaudatum gen. n., sp. n. is closest to Alloionema appendiculatum, another gastropod associate. It is differentiated from A. appendiculatum by the presence of an outstretched vs reflexed testis and the absence of denticles in the stoma, by the parasitic juv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Juveniles inhabiting the pallial cavity (a double fold of the mantle which encloses a water space) vs the foot was one of the characters used to differentiate Neoalloionema tricaudatum from A. appendiculatum (Ivanova et al . 2015). However, our above observations suggest that the difference in infection site in the host may not be a reliable character to differentiate these two nematode species.…”
Section: Discussionmentioning
confidence: 99%
“…Juveniles inhabiting the pallial cavity (a double fold of the mantle which encloses a water space) vs the foot was one of the characters used to differentiate Neoalloionema tricaudatum from A. appendiculatum (Ivanova et al . 2015). However, our above observations suggest that the difference in infection site in the host may not be a reliable character to differentiate these two nematode species.…”
Section: Discussionmentioning
confidence: 99%
“… This study A. similis ITD226 KX185598 D. reticulatum This study A. similis ITD294 KX185599 L. valentiana This study A. similis ITD295 KX185600 L. valentiana This study Neoalloionema indicum KP204845 KP204847 Félix Lab Nermuť et al ( 2015 ) Neoalloionema tricaudatum KR817916 KR817917 Cyclophorus sp. Ivanova et al ( 2016 ) a Arion vulgaris (= Arion lusitanicus ) …”
Section: Methodsmentioning
confidence: 99%
“…1), and P. neopapillosa, P. californica and P. papillosa have been observed to demonstrate parasitising preferences for several slug species, including D. reticulatum, D. invadens, L. valentiana, A. ater, A. vulgaris and A. hortensis [39][40][41][42]. Moreover, international surveys have been conducted in Europe [7], Asia [43], North America [44], Australia [45] and Africa [46] to identify whether nematodes from other families are associated with molluscs as definitive hosts. Overall, it has been reported that nematode species belonging to the following eight families-Agfidae, Alaninematidae Alloionematidae, Angiostomatidae, Cosmocercidae, Diplogasteridae, Mermithidae and Rhabditidae used molluscs as definitive hosts [40,[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65].…”
Section: Nematodes As a Biocontrol Agent Of Slugsmentioning
confidence: 99%